The Identification of Somatic Mutations in Interferon-G Signal Molecules in Human Uterine Leiomyosarcoma - Takuma Hayashi; Tomoyuki Ichimura; Hirofumi Ando; Koichi Ida; Miki Kawano; Tanri Shiozawa; Susumu Tonegawa; Yae Kanai; Hiroyuki Aburatani; Nobuo Yaegashi; Ikuo Konishi (Journal of Cancer Genetics And Biomarkers, 2016)
Human uterine leiomyosarcoma (LMS) is neoplastic malignancy that typically arises in tissues of mesenchymal origin. The identification of novel molecular mechanism leading to human uterine LMS formation and the establishment of new therapies has been hampered by several critical points. We earlier reported that mice with a homozygous deficiency for proteasome beta subunit 9 (PSMB9)/b1i, an interferon (IFN)-g inducible factor, spontaneously develop uterine LMS. The use of research findings of the experiment with mouse model has been successful in increasing our knowledge and understanding of how alterations, in relevant oncogenic, tumour suppressive, and signaling pathways directly impact sarcomagenesis. The IFN-g pathway is important for control of tumour growth and invasion and, has been implicated in several malignant tumours. In this study, experiments with human tissues revealed a defective PSMB9/b1i expression in human uterine LMS that was traced to the IFN-g pathway and the specific effect of somatic mutations of Janus kinase (JAK1) molecule or promoter region on the transcriptional activation of PSMB9/b1i gene. Understanding the molecular mechanisms of human uterine LMS may lead to identification of new diagnostic candidates or therapeutic targets in human uterine LMS.
Keywords: PSMB9/b1i